Research on aroma components in flowers and fruits of three varieties of jaboticaba - QIU Shanlian; LIN Baomei; WU Miaohong; HONG Jiamin; ZHENG Kaibin (浙江大学学报. 农业与生命科学版, 2021)
The flowers and fruits of three varieties of jaboticaba including ‘Saba’ (‘Sb’), ‘Sijizaosheng’ (‘Sjzs’) and ‘Fukuoka’ were used to determine the aroma components by using head space-gas chromatography-mass spectrometry (HS-GC-MS) technology. The results showed that the floral and fruit aroma components of the three varieties had their own characteristics. A total of 48 kinds of floral aroma substances were detected in the three varieties, and terpenes were the main components. Thirty-five kinds of floral aroma components were identified in ‘Sb’, and the main components were monoterpenes, including α-pinene (22.01%), β-pinene (20.41%), D-limonene (19.86%), β-ocimene (12.18%) and etc.; 26 kinds of floral aroma components were identified in ‘Sjzs’, which were mainly consisted of the sesquiterpenes of β-caryophyllene (25.45%), β-cyclogermacrane (10.25%), the monoterpenes of β-pinene (11.08%), α-pinene (8.96%) and etc.; 19 kinds of floral aroma components were identified in ‘Fukuoka’, and the main components were β-caryophyllene (53.40%), β-cyclogermacrane (13.55%), β-ocimene (15.81%) and etc. A total of 32 kinds of fruit aroma substances were detected in the three varieties, and terpenes were also the main components. Fourteen kinds of fruit aroma components were identified in ‘Sb’, and the main components were the monoterpenes of D-limonene (15.48%), β-ocimene (10.64%), and β-pinene (10.53%), the sesquiterpene of cubebene (14.05%) and etc. Twenty-six kinds of fruit aroma components were identified in ‘Sjzs’, mainly consisted of the sesquiterpenes of cubebene (15.49%), β-caryophyllene (13.19%), (－)-α-neoclovene (12.83%) and etc. Thirteen kinds of fruit components were identified in ‘Fukuoka’, and the main components were β-caryophyllene (41.21%), (－)-α-neoclovene (14.51%) and etc. The content of esters in ‘Sjzs’ flower (10.48%) was significantly higher than that in the other two varieties, and the content of esters in ‘Sb’ fruit (14.80%) was significantly higher than that in the other two varieties. ‘Sjzs’ and ‘Fukuoka’ had a higher similarity (0.845) of floral aroma components, and ‘Fukuoka’ had a higher similarity (0.893) between floral aroma and fruit aroma components than the other two varieties.